Photophysics of singlet and triplet intraligand excited states in [ReCl(CO)3(1-(2-pyridyl)-imidazo[1,5-α]pyridine)] complexes - Blanco-Rodríguez, Ana María; Kvapilová, Hana; Sýkora, Jan; Towrie, Michael; Nervi, Carlo; Volpi, Giorgio; Záliš, Stanislav; Vlček, Jr, Antonín (Journal of the American Chemical Society, 2014)
Excited-state characters and dynamics of [ReCl(CO)3(3-R-1-(2-pyridyl)-imidazo[1,5-α]pyridine)] complexes (abbreviated ReGV-R, R = CH3, Ph, PhBu(t), PhCF3, PhNO2, PhNMe2) were investigated by pico- and nanosecond time-resolved infrared spectroscopy (TRIR) and excited-state DFT and TD-DFT calculations. Near UV excitation populates the lowest singlet state S1 that undergoes picosecond intersystem crossing (ISC) to the lowest triplet T1. Both states are initially formed hot and relax with ∼20 ps lifetime. TRIR together with quantum chemical calculations reveal that S1 is predominantly a ππ* state localized at the 1-(2-pyridyl)-imidazo[1,5-α]pyridine (= impy) ligand core, with impy → PhNO2 and PhNMe2 → impy intraligand charge-transfer contributions in the case of ReGV-PhNO2 and ReGV-PhNMe2, respectively. T1 is predominantly ππ*(impy) in all cases. It follows that excited singlet and corresponding triplet states have to some extent different characters and structures even if originating nominally from the same preponderant one-electron excitations. ISC occurs with a solvent-independent (CH2Cl2, MeCN) 20-30 ps lifetime, except for ReGV-PhNMe2 (10 ps in CH2Cl2, 100 ps in MeCN). ISC is 200-300 times slower than in analogous complexes with low-lying MLCT states. This difference is interpreted in terms of spin-orbit interaction and characters of orbitals involved in one-electron excitations that give rise to S1 and T1 states. ReGV-R present a unique case of octahedral heavy-metal complexes where the S1 lifetime is long enough to allow for separate spectroscopic characterization of singlet and triplet excited states. This study provides an insight into dynamics and intersystem crossing pathways of low-lying singlet and triplet excited states localized at bidentate ligands bound directly to a heavy metal atom. Rather long (1)IL lifetimes indicate the possibility of photonic applications of singlet excited states.